The impact of biological and psychosocial factors on the formation of mental disorders in patients who have experienced COVID-19 and exposed to the stressors of the SARS-COV-2 pandemic - N.O. Maruta; V.Y. Fedchenko; I.O. Yavdak; T.V. Panko (Medičnì Perspektivi)
The article is devoted to aspects of the formation of clinical manifestations of mental disorders during the COVID-19 pandemic. The goal – to investigate the clinical and anamnestic features and their impact on the formation of psychopathological consequences in patients with first diagnosed mental disorders who have experienced COVID-19 and exposed to the stressors of the SARS-CoV-2 pandemic. 97 patients with first diagnosed mental disorders who have experienced COVID-19 and exposed to the stressors of the SARS-CoV-2 pandemic were examined and made up the main group. The comparison group included 58 people without mental disorders who have experienced COVID-19 and exposed to the stressors of the SARS-CoV-2 pandemic. During the study, a thorough analysis of the anamnesis of the disease was carried out, including information about the experienced coronavirus disease COVID-19, the impact of the stressors of the SARS-COV-2 pandemic, and the features of the initial psychopathological manifestations. Clinical-psychopathological, clinical-amnestic methods using the developed questionnaire containing questions that reflect the impact of the coronavirus disease COVID-19 and the stressors of the SARS-CoV-2 pandemic on the mental health of the general population, classification of COVID-19 by degree of severity, "empirical" percentage visual scale (KT 0-4), and methods of statistical analysis were applied. The obtained data of a comprehensive study made it possible to distinguish among patients with first diagnosed mental disorders 3 subgroups with characteristic differences in the course and conditions of treatment of the experienced coronavirus disease COVID-19, the structure and significance of the stressors of the SARS-COV-2 pandemic, which the patients encountered, initial psychopathological manifestations. It has been established that the psychopathological consequences of the complex impact of the coronavirus disease COVID-19 and the stressors of the SARS-CoV-2 pandemic lead to the formation of first diagnosed mental disorders in individuals from the general population, among whom the most common forms of mental pathology are depressive episodes, neurotic, associated with stress and somatoform disorders and organic mental disorders. The significance of the obtained data lies in the possibility of studying the role of the psychopathological consequences of COVID-19 in the genesis of mental disorders.